Relaxin-3/RXFP3 networks: an emerging target for the treatment of depression and other neuropsychiatric diseases? - Smith, Craig M.; Walker, Andrew W.; Hosken, Ihaia T.; Chua, Berenice E.; Zhang, Cary; Haidar, Mouna; Gundlach, Andrew L. (Frontiers in Pharmacology, 2014)
Animal and clinical studies of gene-environment interactions have helped elucidate the mechanisms involved in the pathophysiology of several mental illnesses including anxiety, depression and schizophrenia; and have led to the discovery of improved treatments. The study of neuropeptides and their receptors is a parallel frontier of neuropsychopharmacology research and has revealed the involvement of several peptide systems in mental illnesses and identified novel targets for their treatment. Relaxin-3 is a newly discovered neuropeptide that binds and activates the G-protein coupled receptor, RXFP3. Existing anatomical and functional evidence suggests relaxin-3 is an arousal transmitter which is highly responsive to environmental stimuli, particularly neurogenic stressors, and in turn modulates behavioral responses to these stressors and alters key neural processes, including hippocampal theta rhythm and associated learning and memory. Here, we review published experimental data on relaxin-3/RXFP3 systems in rodents, and attempt to highlight aspects that are relevant and/or potentially translatable to the aetiology and treatment of major depression and anxiety. Evidence pertinent to autism spectrum and metabolism/eating disorders, or related psychiatric conditions, is also discussed. We also nominate some key experimental studies required to better establish the therapeutic potential of this intriguing neuromodulatory signaling system, including an examination of the impact of RXFP3 agonists and antagonists on the overall activity of distinct or common neural substrates and circuitry that are identified as dysfunctional in these debilitating brain diseases.